2017
DOI: 10.1002/cncr.30914
|View full text |Cite
|
Sign up to set email alerts
|

The lack of a relationship between physician payments from drug manufacturers and Medicare claims for abiraterone and enzalutamide

Abstract: No difference in prescription count was found to exist between prescribers who received industry payments and those who did not. A positive correlation was noted between industry payments and prescription count for enzalutamide. Ease of adoption may affect differences between the 2 drugs. Cancer 2017;123:4356-62. © 2017 American Cancer Society.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 18 publications
1
17
1
Order By: Relevance
“…These results are consistent with an increasing body of literature finding an association between industry payments and physician prescribing behavior, across multiple medical specialties . Our results are also consistent with the finding that an association between industry payments and physician prescribing may be absent for prostate cancer drugs . The reason for the apparent difference between prostate cancer and other cancer types is an area for future study.…”
Section: Discussionsupporting
confidence: 91%
“…These results are consistent with an increasing body of literature finding an association between industry payments and physician prescribing behavior, across multiple medical specialties . Our results are also consistent with the finding that an association between industry payments and physician prescribing may be absent for prostate cancer drugs . The reason for the apparent difference between prostate cancer and other cancer types is an area for future study.…”
Section: Discussionsupporting
confidence: 91%
“…A study of denosumab and degarelix for prostate cancer demonstrated only a weak association between payments and prescribing habits 9 . Similarly, an analysis of enzalutamide and abiraterone prescribing among urologists and oncologists found no relationship between receipt of payments and prescription counts 8 . These results differ from ours for several possible reasons.…”
Section: Discussionmentioning
confidence: 99%
“…Prior analyses using OPP data have suggested that the receipt of industry payments is associated with increased prescribing costs for some patients 5 and increased prescribing of promoted oral anticoagulants, diabetes drugs, and intraocular anti-VEGF injections 6, 7 . Within urology, previous work has examined the association between payment and prescribing of drugs for prostate cancer 8, 9 . Contrary to studies in other fields, these studies found either a weak or no association between payments and prescribing.…”
Section: Introductionmentioning
confidence: 99%
“…However, studies in a variety of specialties and contexts have shown this to be untrue. 7,[20][21][22][23] Even small amounts of compensation, such as free meals, have been correlated to physician prescription of brand-name drugs, and payments from device companies have been associated with performance of specific procedures. 19 Industry certainly plays a key role in health care.…”
Section: Discussionmentioning
confidence: 99%